Pratiques culturales, valeurs d’usage et perception des paysans des espèces compagnes du cacaoyer dans des agroforêts traditionnelles au centre de la Côte d’Ivoire - Constant Yves Adou Yao; Kouassi Bruno Kpangui; Bi Tra Aimé Vroh; Djakalia Ouattara (Revue d'ethnoécologie)
Cocoa production has long been considered as one of the main causes of forest cover degradation in the tropics. However, studies show more and more often that cocoa-based agroforestry systems host a relativily high diversity of shade species, compared to monoculture plantations. In addition to the goods and services provided by these species, only local farmers' perceptions could allow the maintenance and success of this cultivation system in forest-savanna transition zone, considered as unfavorable for cocoa cultivation. Our study analyses the traditional agroforestry practices in three localities of Kokoumbo in the Centre of Côte d’Ivoire. One hundred and five peasants have been surveyed and we have recorded their utilization of plant species in cocoa plantations and their perceptions of the repercssions on cocoa trees. The resulted data have been completed by botanical inventories in 105 plots of 625 m2 each. The results show that 65 species were recognized by farmers as being compatible or not with the cocoa cultivation. Large trees like Milicia excelsa that would maintain soil fertility or moisture in the environment, were marked favorable to cocoa. The majority of food species had no known effect on cocoa trees. Nesogordonia papaverifera, although commonly found in plantations, was known to dry soil or delay the development of cocoa trees. The mechanisms of these antagonisms were often difficult to explain by farmers. Extensive research taking into account the physical, chemical aspects and even other biological factors, indicators of soil fertility will be necessary to support the knowledge of local cocoa farmers in the study area.